2022
DOI: 10.1172/jci.insight.157034
|View full text |Cite
|
Sign up to set email alerts
|

The whole-cell pertussis vaccine imposes a broad effector B cell response in mouse heterologous prime-boost settings

Abstract: Since the introduction of new generation pertussis vaccines, resurgence of pertussis is observed in many developed countries. Former whole-cell pertussis vaccines (wP) are able to protect against disease and transmission but have been replaced in several industrialized countries 2 because of their reactogenicity and adverse effects. Current acellular pertussis vaccines (aP), made of purified proteins of Bordetella pertussis, are efficient at preventing disease but fail to induce long-term protection from infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…In addition, the study revealed that only immunization with wP vaccine resulted in the generation of B. pertussis -specific memory B cells [ 70 ]. Recent studies also demonstrated that priming mice with wP vaccines led to faster and stronger stimulation of local germinal centers stimulation and memory B cell responses within the dLNs, as well as to plasma cells induced within the bone marrow presenting with a broader antigenic and isotypic diversity, in comparison to prime immunization with aP vaccine [ 71 ]. Importantly, the results indicated that, in contrast to T cell responses, where the first dose of aP vaccine determines the immune response to a boost vaccination with wP, the B cell profile and antibody production induced by aP were re-oriented by a wP boost and led to induction of Ab with a broader isotypic diversity [ 71 ].…”
Section: Acellular and Whole-cell Pertussis Vaccine Induce Different ...mentioning
confidence: 99%
“…In addition, the study revealed that only immunization with wP vaccine resulted in the generation of B. pertussis -specific memory B cells [ 70 ]. Recent studies also demonstrated that priming mice with wP vaccines led to faster and stronger stimulation of local germinal centers stimulation and memory B cell responses within the dLNs, as well as to plasma cells induced within the bone marrow presenting with a broader antigenic and isotypic diversity, in comparison to prime immunization with aP vaccine [ 71 ]. Importantly, the results indicated that, in contrast to T cell responses, where the first dose of aP vaccine determines the immune response to a boost vaccination with wP, the B cell profile and antibody production induced by aP were re-oriented by a wP boost and led to induction of Ab with a broader isotypic diversity [ 71 ].…”
Section: Acellular and Whole-cell Pertussis Vaccine Induce Different ...mentioning
confidence: 99%
“…This study builds on other studies on heterologous prime-boost immunization, against Y. pestis ( 69 ) or other pathogens ( 70 73 ), showing major differences in immunity depending on which formulation is administered first. Our studies found that female mice were more protected than males by these heterologous vaccines, whether they included pgm- pPst- Δ yopD /Δ caf1 , pgm- pPst- Δ caf1 , or CO92 Δ yscN + C12 Δ yscN as the LAV.…”
Section: Discussionmentioning
confidence: 95%